Local Infiltration Analgesia for Postoperative Pain Control following Skin Crease “Bikini Incision” Anterior Total Hip Arthroplasty for Neglected Femoral Neck Fractures - Angelico Gabriel Lorena; Joel Baron (Philippine Journal of Orthopaedics)
Background. The incidence of femoral neck fractures continues to increase along with the rise of the elderly population, and in the Philippines, a significant number have become neglected. Total hip arthroplasty (THA) is the treatment of choice for previously healthy and active patients. Local infiltration analgesia is a known adjunct for postoperative pain control, but its effects for THA via the “bikini incision” anterior approach are yet to be established.